Johann Nikolaus Tetens’ Critical Foundations of the First Project for the Reform of Metaphysics - Secundant, Sergii; Sanchez-Rodrigez, Manuel (Sententiae, 2024)
Tetens is usually considered the main representative of English empiricism in 18th-century German philosophy. In order to find out how fair this characterization is, the authors turn to the analysis of the critical foundations of the project of reform of metaphysics proposed by Tetens in his early article “Reflections on Some Reasons Why There Are So Few Settled Truths in Metaphysics” (1760). Having analyzed the arguments of this article, the authors prove: 1) Tetens’s project for the reform of philosophy fully fits into the tradition of German "methodical" philosophy, 2) it is based on the methodological and epistemological principles of the philosophy of Leibniz and Wolf, and is aimed at substantiating the basic provisions of Leibniz’s metaphysics, 3) Tetens’s “observing method” is rooted in the philosophy of Leibniz and Wolf, and not in the tradition of English empiricism.